ECONOMIC VALUATION OF A NATURAL RECREATION AREA: THE VULCANOTOUR IN MERAPI VULCANO - Latri Wihastuti; Chandra Utama (Center for Economic Studies Universitas Katolik Parahyangan, 2019)
Daerah Istimewa (the special province of) Yogyakarta or usually abbreviated as DIY is the second biggest tourism destination in Indonesia, after Bali. DIY has more than 100 recreation sites. One of the famous recreation sites in DIY is Vulcanotour (VT) located in the area of Merapi Vulcano. This paper employed the individual travel cost method ITCM) to estimate the economic value of VT. We used OLS, Non-linear Normal/NLS, Poisson, and Negative Binomial methods to estimate the regression. This study used primary data from the management of VT and 60 visitors in the period of April to May 2013. The study found that the number of visits to VT was significantly affected by the number of trips to Yogyakarta City (the capital city of DIY). The economic value per visit of VT were ranged from USD 33.1 to USD 153.4. The study also concluded that the number of trips to VT is significantly influenced by the Yogyakarta city as a destination. In other words, the VT cannot be separated from other recreation destinations in DIY.Keywords: Natural recreation area; Individual Travel Cost Method (ITCM); Merapi Vulcano; Vulcanotour; Yogyakarta